Between Imitation and Thematization of Music: Towards an Intermedial Utopia in Late German Modernist Literature (Филологический класс, 2021)
The paper seeks to reveal how the issue of “transgressions between literature and music” (U. Weimann) corresponds to the modern epistemological, medial, and poetological ideas. The object of the study is intermedial utopias. Using representative poetic and prose German texts of the twentieth century as examples, the author describes the ambivalent cultural situation of modernity, characterized by a tendency of literature towards the abstract thinking of music and hypertrophied sound recording, while music develops from “Wagnerian music as language” (T. Adorno) to the “absolute music” or performative acoustic phenomena of New Music. The aim of the study is to identify typical forms of intermedial verbal-musical utopia in late German modernist literature. The study uses the comparative, narratological and musicological methods, the qualitative analysis of verse forms and the thematic analysis of prose. In the course of her research, the author makes a conclusion that there are three ways of “literary music making”, such as: telling about music (T. Mann, H. Hesse, M. Beyer, P. Süskind), imitating the musical language (as performed by avant-gardists) or as a combination of these two models (H. Wollschläger, T. Bernhard, E. Jelinek etc.). In German modernism and postmodernism, this intermedial transfer is complicated by ethical and political collision, which has its origins in utopian romantic thinking, and which became increasingly acute during the Third Reich era (cf. Thomas Mann’s and Hans Wollschläger’s reconstruction of the devil’s pact fable). Music becomes a form of escape into the metaphysics, while a musical composition is chosen as an alternative to traditional lyrical or narrative forms. Thus, this collision is considered in the context of the modernist crisis and criticism of language. The results of this study can be used in the formation of an alternative history of literature based not only on the evolution of verbal forms, but also on hybrid genres, namely, verbal-musical forms.